Molecular epidemiology and clinical‐laboratory aspects of chromoblastomycosis in Mato Grosso, Brazil. Issue 12 (29th September 2022) - Guevara, Armando; Nery, Andréia Ferreira; de Souza Carvalho Melhem, Márcia; Bonfietti, Lucas; Rodrigues, Anderson Messias; Hagen, Ferry; de Carvalho, Jamile Ambrósio; de Camargo, Zoilo Pires; de Souza Lima, Bruna Jacomel F.; Vicente, Vânia Aparecida; Hahn, Rosane Christine
Abstract: Introduction: Chromoblastomycosis is a disease caused by melanized fungi, primarily belonging to the genera Fonsecaea and Cladophialophora, mainly affecting individuals who are occupationally exposed to soil and plant products. This research aimed to determine the clinical, epidemiological and laboratory characteristics of chromoblastomycosis in the state of Mato Grosso, Brazil. Materials and Methods: Patients diagnosed with chromoblastomycosis treated at the Júlio Müller University Hospital, Cuiabá, Brazil, from January 2015 to December 2020, whose isolates were preserved in the Research Laboratory of the Faculty of Medicine of the Federal University of Mato Grosso. Isolates were identified by partly sequencing the Internal Transcribed Spacer (ITS) and β‐tubulin ( BT2 ) loci. AFLP fingerprinting was used to explore the genetic diversity. Susceptibility to itraconazole, voriconazole, 5‐fluorocytosine, terbinafine and amphotericin B was determined by the broth microdilution technique. Results: Ten patients were included, nine were male (mean age = 64.1 years). Mean disease duration was 8.6 years. Lesions were mainly observed in the lower limbs. Predominant clinical forms were verrucous and scarring. Systemic arterial hypertension and type II diabetes mellitus were the predominant comorbidities. Leprosy was the main concomitant infectious disease. Fonsecaea pedrosoi was the unique aetiological agent identified with moderate genetic diversity ( H  = 0.3934–0.4527; PIC  = 0.3160–0.3502). Antifungal agents with the highest activity were terbinafine, voriconazole and itraconazole. Conclusion: Chromoblastomycosis is affecting the poor population in rural and urban areas, mainly related to agricultural activities, with F. pedrosoi being the dominant aetiologic agent. All isolates had low MICs for itraconazole, voriconazole and terbinafine, confirming their importance as therapeutic alternatives for chromoblastomycosis.